A Non-Scalpel Technique for Minimally Invasive Surgery: Percutaneously Looped Thread Transection of the Transverse Carpal Ligament. (March 2015) - Guo, Danqing; Yu, Tang; Ji, Yizheng; Sun, Tiansheng; Guo, Joseph; Guo, Danzhu
Purpose: This study aims to develop an alternate technique for improving the surgical procedure of carpal tunnel release. Method The transverse carpal ligament is transected by utilizing a piece of thread looped percutaneously under the visualization of ultrasound. The procedure, the thread carpal tunnel release (TCTR), was performed on 34 hands of 20 patients. Self-administrated Levine-Katz questionnaire was used for assessing the symptom severity and functional status of the outcomes. Results: TCTR was performed in each case with no unintended consequences. The average duration for a procedure was 7 min, excluding time of preparation. Significant improvements in subjective sensibility were reported within 24 h, and sleep quality improved for all cases. There were no postoperative complications. The scores of questionnaire 3 months postoperatively were comparable to the literature controls. Conclusion: TCTR is a safe and effective minimally invasive surgery performed under local anesthesia in a clinic-based procedure room and results in only one-needle entrance point at the wrist and one-needle exit point in the palm. The feature of the procedure includes the potentials of reduced risk of iatrogenic injury, reduced surgical cost, and reduced patient recovery time. The study has shown encouraging promise for optimizing the technique of carpal tunnel release, and more clinical trials are necessary to confirm the findings.